Динаміка двоперехідного нарізання зубчастих коліс черв’ячними фрезами в автоматичному циклі - Грицай, І. Є. (Видавництво Державного університету "Львівська політехніка", 2000)
Outcomes of mathematical simulation of parameters of sections, components of force of cutting and torque during cutting cylindrical cog-wheels by screw type hobs. The possibility of a heightening of efficiency and quality of manufacture of cog-wheels is theoretically confirmed at use of screw type hobs with the modified profile of a cog.